Thematic workshop: spices, the chemistry in small details (Research, Society and Development, 2020)
The present work is an excerpt from a dissertation that defends the use of means of scientific dissemination in a formal teaching context. The research is of a qualitative nature, where a case study was carried out, with the planning of a Thematic Workshop together with graduates in chemistry, members of PIBID, entitled “Spices: Chemistry present in the Small Details”. The objective of this activity was to verify how scientific dissemination can contribute to the teaching of chemistry. To develop the Thematic Workshop, some didactic resources were used, among them, the reading and discussion of a Scientific Dissemination Text; demonstrative lecture with the aid of experimentation and the application of a didactic game. The purpose of the proposal was to provide students with contextualized learning, in order to qualify the use of chemical language and promote scientific literacy.